Unusual skin manifestations associated with parvovirus B19 primary infection in children. Issue 6 (19th September 2018) - Ferrari, Bruno; Díaz, María Sol; López, Micaela; Larralde, Margarita
Abstract: Parvovirus B19 is a DNA virus of the Parvoviridae family. We present four children with unusual exanthems associated with parvovirus infection: a purpuric periflexural pattern, a purpuric vasculitic pattern, and a combination of the two.